TINGKAT PENGETAHUAN DAN DUKUNGAN KELUARGA TERHADAP PERAWATAN LANJUTAN PADA NEONATUS YANG MENGALAMI KEGAWATAN NAFAS DI RUANG NICURSUD PROF. H. ALOEI SABOE KOTA GORONTALO - Nyimas Heni; Anik Indarwati (program studi ilmu keperawatan fakultas ilmu kesehatan universitas muhammadiyah gorontalo, 2021)
Natural Neonatus is breath serious condition need action immediately that is resusitasi, for that nurse in NICU have to can conduct action resusitasi. Target of this research is to know picture knowledge of nurse about resusitasi at natural neonatus is breath serious condition inroom of NICU RSUD. Prof. Dr. Hj. Aloe Saboe Town of Gorontalo. This Population Research is nurse of room of NICU RSUD. Prof. Dr. Hj. Aloe Saboe Town of Gorontalo amount to 35 people with technique intake of sampel the used is total technique of sampling Result of research indicate that knowledge of nurse [in] Room of NICU RSUD Prof. Dr. Hi, Aloei Saboe Town of Gorontalo about breath serious condition and action of resusitasi atnatural neonatus isexhalation serious condition most included in category enough that is equal to 46% from 35 responder people or 16 responder people. If final score summed by hence got by average value 73,6 or included in category enough. This meaningful matter that most nurse have pegetahuan which enough about managery at neonatus with exhalation serious condition.Pursuant to this research is suggested to nurse of NICU shall always improve and update action and knowledge of resusitasi so that earn swiftly and precisely overcome natural neonatus is exhalation serious condition.